2017
DOI: 10.1021/acs.inorgchem.7b00894
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium(I) Tricarbonyl Complexes with (2-Hydroxyphenyl)diphenylphosphine as PO Bidentate Ligand

Abstract: In the present work, we investigated potential means to obtain neutral tricarbonyl mixed-ligand fac-[M(CO)LL] complexes (M = Re, Tc) containing the (2-hydroxyphenyl)diphenylphosphine (POH) bidentate ligand (LH) and a series of monodentate ligands (L). First, fac-[Re(CO)(PO)(HO)], 1, was synthesized by reaction of POH and [EtN][Re(CO)Br] in equimolar amounts in MeOH at room temperature. Interestingly, with excess of POH this reaction afforded fac-[Re(CO)(PO)(POH)], 2, with POH operating both as a bidentate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
0
18
0
2
Order By: Relevance
“…The peak at m/z 581 is due to the rearranged ion [Re(CO) 3 (PO)(MeOH) + H] + originating by exchange of water with methanol used as solvent. Cluster ion peaks at m/z 827, 843 and 1095 correspond to the rearranged molecule [Re(CO) 3 (PO)(POH) + H] + (exchange of water for POH generated by partial hydrolysis of complex 1 ; vide infra , complex 6 ), its oxidized adduct ([Re(CO) 3 (PO)(O=POH) + H] + generated by partial decomposition of complex 1 followed by in situ oxidation of POH) and the dimeric species, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak at m/z 581 is due to the rearranged ion [Re(CO) 3 (PO)(MeOH) + H] + originating by exchange of water with methanol used as solvent. Cluster ion peaks at m/z 827, 843 and 1095 correspond to the rearranged molecule [Re(CO) 3 (PO)(POH) + H] + (exchange of water for POH generated by partial hydrolysis of complex 1 ; vide infra , complex 6 ), its oxidized adduct ([Re(CO) 3 (PO)(O=POH) + H] + generated by partial decomposition of complex 1 followed by in situ oxidation of POH) and the dimeric species, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Rhenium (I) tricarbonyl complexes 1 – 7 were prepared according to published procedures . HPLC‐grade solvents were purchased from Sigma‐Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, where M is Re or 99m Tc, L 1 is a bidentate ligand (bipyridine, 2-picolinic acid, acetylacetone, etc) and L 2 is a monodentate ligand (aqua, imidazole, phosphine or isocyanide), have been studied extensively for the development of novel radiopharmaceuticals for diagnosis (M = 99m Tc) or radiotherapy (M = 186/188 Re) (Knopf et al, 2017;Mundwiler et al, 2004;Papagiannopoulou et al, 2014;Triantis et al, 2013;Shegani et al, 2017). Furthermore, recent studies have revealed the potential of such fac-[Re(CO) 3 L 1 L 2 ] complexes as anticancer agents (Leonidova & Gasser, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Τα κύρια ισότοπα του ρηνίου και των γειτονικών του στοιχείων καθώς και κάποιες ιδιότητες τους φαίνονται στην Εικόνα 1.1. 9 Τα ισότοπα 186 Re (εκπομπή β -, t1/2 = 90 ώρες, Εmax = 1.07 MeV, εμβέλεια ιστού 5 mm) και 188 Re (εκπομπή β -, t1/2 = 17 ώρες, Εmax = 2.1 MeV, εμβέλεια ιστού 11 mm) έχουν φυσικές ιδιότητες (Πίνακας 1.1) που τα κάνουν πολύ ελκυστικά για τη ραδιοθεραπεία του καρκίνου. 10,11 Ιδιαίτερη έμφαση έχει δοθεί στο 188 Re το οποίο μπορεί να παραληφθεί από γεννήτρια βολφραμίου -188 (t1/2 = 69 μέρες) (Σχήμα 1.1).…”
Section: τα ισότοπα του ρηνίουunclassified